(untitled) (Linguostylistic Studies, 2015)
The register of nominations, forming the nominative field child in Lesya Ukrainka’s epistolary texts, is defined; the main attention is paid to the names with occasional status, most of them were the elements of Kosach-Dragomanov’s family metalanguage with differential nature, being as mean of its brothers and sisters’ – native and cousins (mostly – earlier), and also newhevs’ identification: Maka, Kna-kna, Puts, Putsyk, Putylda, Lyleia, Husia, Husynia, Husynka, Drozd, Drozdyk, Kokh, Kakhota, Patia, Putia, Riuryk, Zoria, Lydyk, Lydianko, Mausyk, Tiusynia, Ymochka, lyleniatko etc.; most of such nominations are applied as general for all or few children, for example, busliata, verchyky, draby, lyseniata, nehry, putsy, tyhry, tyhry-nehry, tyhro-nehry, khrushchyky, shchuchyky; motivation and productive models of stylisticallypaintednominations were defined, first of all individually impressive; the lists of occasional nominations of each child in Kosach family, used in Lesya Ukrainka’s epistolary dialogues, were made more accurate. Key words: occasionalism, nominative field, nomination, lexical regulative, epistolary text, child. References